Development of PLA/HA porous scaffolds with controlled pore sizes using the combined freeze drying and sucrose leaching technique for bone tissue engineering - SINGHAWANNURAT, Sunisa; LAWTAE, Panuwat; ROJVIRIYA, Catleya; PHOOVASAWAT, Chalermluck (Journal of Metals, Materials and Minerals, 2024)
The combination of freeze drying and sucrose leaching technique was employed to fabricate PLA/HA scaffolds with controlled pore size. The influence of the HA content and sucrose size on the scaffold properties was investigated. The fabricated scaffolds showed porous properties with a porosity of 44% to 58% and pore size of 461 μm to 688 μm. The results indicated that the scaffolds possessed favorable porous properties, illustrated by good interconnectivity, appropriate pore size, and suitable porosity. These characteristics were crucial for facilitating bone cell growth and promoting the formation of new tissue within the scaffold structure. The compressive modulus of the scaffolds was examined and found to be in the range of 3.35 MPa to 5.75 MPa. Furthermore, the degradation behavior of the scaffolds was studied for 28 days in a Phosphate Buffered Saline solution. The results showed that the degradation rate was varied in the range of 6% to 14%. The water uptake of the scaffolds exhibited a range between 180% and 200%. Enhancement in water uptake was observed with higher HA content and increased sucrose size. Consequently, the scaffolds developed in this study hold promise as optimal candidates for bone tissue engineering applications.